Estudio de prefactibilidad para la instalación de un servicio de limpieza criogénica con hielo seco para el sector de generación de energía eléctrica - Suárez Koch, Jimena Josceline (2020)
The main objective of this work is to determine the technological, economic, financial and market viability for the implementation of a cryogenic cleaning service with dry ice for the energy generation sector.